ANALISIS PENGARUH FRAUD HEXAGON TERHADAP FRAUDULENT FINANCIAL REPORTING MENGGUNAKAN METODE BENEISH M-SCORE (Studi Empiris pada Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021) - Dhanka Brianta Ginting; Daljono Daljono (Diponegoro Journal of Accounting, 2023)
This research aims to analyze and examine the effect of the fraud hexagon theory which is classified by financial target, financial stability, external pressure, ineffective monitoring, change in auditor, change in director, arrogance, and political connection on fraudulent financial reporting as measured using Beneish M-Score method. The research is based on various previous results, the phenomenon of fraudulent financial reporting, and a limited number of studies related to the fraud hexagon theory. The population in this study are companies that are listed in the consumer goods industry sector on the Indonesia Stock Exchange. The research sample was sorted based on several predetermined criteria using the purposive sampling method at 49 companies over a period of 3 years from 2019 to 2021. The research used quantitative methods and logistic regression analysis methods with the help of Eviews 10. The results of the research show that external pressure and change in auditor have a positive effect on fraudulent financial reporting, while financial target has a negative effect on fraudulent financial reporting. Meanwhile, financial stability, ineffective monitoring, change in director, arrogance, and political connection have no effect on fraudulent financial reporting.